2015
DOI: 10.5505/megaron.2015.73745
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dijital marketing communication tools to create brand awareness by housing companies

Abstract: Füsun ÇİZMECİ, Tuğçe ERCANCreating brand awareness is the first and most important stage of marketing communication. Many types of marketing communication tools have been used to do this in business processes. Digital marketing tools are actually a deconstruction of traditional marketing tools and have become more important by providing interactivity to both consumers and producers in the marketing process. These tools incorporate consumers into the marketing process as an active, rather than passive, player. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 5 publications
1
55
0
5
Order By: Relevance
“…Previous studies have also shown that awareness relates to action (Baldauf et al, 2003;Cizmeci, 2015). Without adequate awareness, The Food Factor will not be able to share its knowledge to encourage others to change behaviors, as well as achieving other Mississippi State University Extension goals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have also shown that awareness relates to action (Baldauf et al, 2003;Cizmeci, 2015). Without adequate awareness, The Food Factor will not be able to share its knowledge to encourage others to change behaviors, as well as achieving other Mississippi State University Extension goals.…”
Section: Discussionmentioning
confidence: 99%
“…Brand awareness exists along a continuum from a simple recognition to an in-depth knowledge of the brand (Momany & Alshboul, 2016). It does not only include the brand name or being previously exposed to it, but it can also mean that consumers can link the logo, name, and other connotations to the brand (Cizmeci, 2015).…”
Section: The Food Factormentioning
confidence: 99%
See 3 more Smart Citations